2008
DOI: 10.1177/0093854808322744
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Inmates in an Adult Prison System

Abstract: Rates of disciplinary misconduct and violence among juvenile male inmates ( N = 703) admitted to a state prison system from 1998 to 2002 are retrospectively examined. The prevalence and frequency of prison misconduct and violence are higher among juveniles than comparison groups of nearest age youthful adults ( N = 3,640) and adult prisoners generally ( N = 33,114), and this disparity between juvenile and adult inmates increases along with the severity of violence. This relationship is found to hold true even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(21 citation statements)
references
References 39 publications
1
18
0
2
Order By: Relevance
“…With regard to age, this finding might be due to the fact that the inmates in the present sample were only 14–25 years old, whereas other researchers used samples with a considerably greater age range (e.g. Kuanliang et al, 2008: 13–40+ years; Lahm, 2008: 18–71 years). Regarding the weak association of migration background and prison violence, the result of this research is in line with some previous studies that reported non-significant associations of ethnicity and inmate-on-inmate violence when controlling for other variables, for example, prior gang involvement and criminal history (MacDonald, 1999; Sorensen and Cunningham, 2007).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…With regard to age, this finding might be due to the fact that the inmates in the present sample were only 14–25 years old, whereas other researchers used samples with a considerably greater age range (e.g. Kuanliang et al, 2008: 13–40+ years; Lahm, 2008: 18–71 years). Regarding the weak association of migration background and prison violence, the result of this research is in line with some previous studies that reported non-significant associations of ethnicity and inmate-on-inmate violence when controlling for other variables, for example, prior gang involvement and criminal history (MacDonald, 1999; Sorensen and Cunningham, 2007).…”
Section: Discussionmentioning
confidence: 65%
“…Age has consistently been found to be negatively correlated with violent misconduct, indicating that younger inmates are particularly likely to engage in physical assaults against other inmates. Kuanliang et al (2008), for example, found that among a large sample of male inmates in the state prison system, juveniles exhibited higher rates of violent misconduct and assault than adult offenders. Furthermore, the difference between young and adult offenders increased with the increasing severity of misconduct.…”
Section: Importation Factorsmentioning
confidence: 99%
“…Adaptacijos veiksnių tyrimai atskleidė atskirų tiek deprivacijos, tiek perkėlimo veiksnių grupėms priskiriamų veiksnių svarbą. Buvo nustatyta, kad prastesne adaptacija pasižymi neseniai atvykę į pataisos įstaigą (Zamble & Porporino, 1988) arba ilgesnes laisvės atėmimo bausmes gavę (MacKenzie & Goodstein, 1985;Kuanliang, Sorensen, & Cunningham, 2008) nuteistieji. Su didesniu patiriamu stresu yra siejamas ir laikotarpis prieš išleidimą iš pataisos įstaigos (Ginneken, 2015).…”
Section: Adaptacijos Pataisos įStaigoje Teoriniai Modeliaiunclassified
“…Dar daugelis autorių (Souza & Dhami, 2010;Warren et al, 2004;Kovács et al, 2019) teigia, kad blogesne adaptacija pasižymi tie nuteistieji, kurie į pataisos įstaigą pateko pirmą kartą, nes jie dar nėra perpratę pataisos įstaigos taisyklių, nežino, ko tikėtis iš įkalinimo patirties, ir t. t. Tačiau šiame tyrime nerasta skirtumų tarp tų tyrimo dalyvių, kurie į pataisos įstaigą pateko pirmą kartą ar pakartotinai. Taip pat ne viename tyrime (MacKenzie & Goodstein, 1985;Kuanliang et al, 2008) atskleista, jog ilgesnes bausmes gavę nuteistieji pasižymi blogesne adaptacija, tačiau šiame tyrime nerasta ryšių tarp pasirinktų adaptacijos rodiklių ir laisvės atėmimo bausmės trukmės. Amžius taip pat nesisiejo nė su vienu šiame tyrime pasirinktu adaptacijos pataisos įstaigoje rodikliu, tačiau svarbu atkreipti dėmesį, kad ir ankstesniuose tyrimuose (Vasile et al, 2010;Porporino & Zamble, 1984) aptinkama tik sąsajų tarp jaunesnio amžiaus ir pataisos įstaigoje padarytų nusižengimų, o šis rodiklis šiame tyrime nebuvo vertintas.…”
Section: Rezultatų Aptarimasunclassified
“…Most research on institutional behavior, however, focuses on either the adult population in the criminal justice system (Steiner & Wooldredge, 2013) or juveniles in juvenile facilities (DeLisi et al, 2009; MacDonald, 1999; Trulson, DeLisi, & Marquart, 2011). Only a few studies have examined the behavior of juveniles in adult prisons, and these studies focused on comparing samples of juveniles with adults, thus limiting understanding of the variation among juveniles (Kuanliang, Sorensen, & Cunningham, 2008; Leigey & Hodge, 2013; McShane & Williams, 1989; Tasca, Griffin, & Rodriguez, 2010). Understanding variation in prison behavior within a sample of juveniles in adult prisons can both add to the development of theoretical frameworks and to debates over policies and practices that place juveniles in adult prisons, especially younger juveniles.…”
mentioning
confidence: 99%